Personal Hygiene Relationship with Complaints on Skin Disorders Farmers in the Alalak Utara Village, Banjarmasin City - uni afriyanti (Health Media, 2019)
Personal hygiene is self-care done to maintain health both physically and psychologically. A clean body minimizes the risk of someone contracting an illness. The purpose of this study was to determine the relationship between personal hygiene and complaints of skin disorders in farmers. The population is study were all farmers in the Alalak Utara Village of Banjarmasain. The sample is study was 30 respondents. The results of data analysis showed that there were complaints of skin disorders in 8 respondents (88.9%), with poor personal hygiene,. While for those who have no complaints of skin disorders 1 respondent (11.1%) with less personal hygiene, 3 respondents (37.5%) with sufficient personal hygiene, and 7 respondents (53.8%) with good personal hygiene. The results of the statistical test show the value of p = 0.046 that there is relationship between personal hygiene and complaints of skin disorders in farmers in the North Alalak Village, Banjarmasin